Role of dermoscopy in the diagnosis of alopecia - Mani, Shoba; Manickam, Navakumar; Gopalan, Kannan; vellaisamy, Seethalakshmi Ganga (Journal of Pakistan Association of Dermatologists, 2018)
Objective The aim of the study was to evaluate the dermoscopic findings in various types of alopecia. Methods A total of 100 patients presenting with alopecia were subjected to dermoscopy with a videodermoscope of magnification 50X and 200X. Results Among 100 patients studied, 21 had alopecia areata (AA), 38 had male androgenetic alopecia (MAGA), nine had female androgenetic alopecia (FAGA), 27 had telogen effluvium (TE), and five had cicatricial alopecia. The most common dermoscopic findings observed in AA were black dots (76%), short vellus hairs (71%) and broken hairs (67%). More than 20% hair diameter diversity (HDD) was observed in the affected areas of all male and female AGA cases. Pigment incontinence, follicular keratotic plugging and follicular effacement were seen in both discoid lupus erythematosus (DLE) and lichen planopilaris (LPP). The characteristic dermoscopic findings in DLE were red dots and arborising red lines. Peripilar cast was the specific finding for LPP. Conclusion Each type of alopecia has unique dermoscopic findings and this facilitates the diagnosis of alopecia. Pili bifurcati like finding was noted in AA.